2020
DOI: 10.3389/fmed.2020.00477
|View full text |Cite
|
Sign up to set email alerts
|

The Corrected Serum Sodium Concentration in Hyperglycemic Crises: Computation and Clinical Applications

Abstract: In hyperglycemia, hypertonicity results from solute (glucose) gain and loss of water in excess of sodium plus potassium through osmotic diuresis. Patients with stage 5 chronic kidney disease (CKD) and hyperglycemia have minimal or no osmotic diuresis; patients with preserved renal function and diabetic ketoacidosis (DKA) or hyperosmolar hyperglycemic state (HHS) have often large osmotic diuresis. Hypertonicity from glucose gain is reversed with normalization of serum glucose ([Glu]); hypertonicity due to osmot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 259 publications
(160 reference statements)
0
22
0
1
Order By: Relevance
“… 8 Corrected serum sodium provides a useful tool for monitoring and management during acute hyperglycemic crises by assessing the magnitude of the deficit of sodium and water and thus provides an initial estimate of the tonicity of the replacement fluids during the course of therapy. 9 The corrected sodium for case 2 was 128 mmol/L and with this hypertonic saline should not have been given and hence reduced chances of developing hypernatremia.…”
Section: Discussionmentioning
confidence: 98%
“… 8 Corrected serum sodium provides a useful tool for monitoring and management during acute hyperglycemic crises by assessing the magnitude of the deficit of sodium and water and thus provides an initial estimate of the tonicity of the replacement fluids during the course of therapy. 9 The corrected sodium for case 2 was 128 mmol/L and with this hypertonic saline should not have been given and hence reduced chances of developing hypernatremia.…”
Section: Discussionmentioning
confidence: 98%
“…The Edelman study has a few limitations. [Na] SW was not corrected for the degree of glycemia ( 17 ). In addition, formula 1, which describes a steady state, provides no information about the time to equilibrium during dynamic periods and does not include factors other than TBNa, TBK, or TBW measured in the steady state that could affect rapidly changing [Na] SW during development or treatment of dysnatremias.…”
Section: Reviewmentioning
confidence: 99%
“…Not accounting for the degree of hyperglycemia in studies of dysnatremias, i.e., using the measured [Na], provides false information about the relationship among body sodium, potassium, and water. The corrected [Na], i.e., a predicted [Na] value after the correction of hyperglycemia, provides an appropriate estimate of this relationship ( 56 ). Katz ( 57 ) calculated theoretically a decrease in [Na] equal to 1.6 mmol/L for each 5.6 mmol/L rise in serum glucose concentration.…”
Section: Reviewmentioning
confidence: 99%
“…Subsequently, the proposed range of coefficients for the calculation of the corrected [Na] was from 1.35 to 4.00 mmol/L reduction in [Na] for every 5.6 mmol/L rise in serum glucose ( 58 ). A review of this topic concluded that Katz's coefficient should be used for calculating the corrected [Na], with exceptions that make monitoring of [Na] and serum glucose during the treatment of hyperglycemia mandatory ( 56 ). The general form of the Al-Kudsi formula ( 59 ), which uses the Katz's coefficient to calculate the corrected [Na], is as follows where both sodium and glucose concentrations are in mmol/L ( 56 ): Several studies on dysnatremias calculated the corrected [Na] using the Al-Kudsi formula ( 30 , 34 , 36 , 41 43 , 46 , 47 , 49 ), and one study excluded from statistical analysis serum glucose levels >7.5 mmol/L ( 51 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation